The Effect of Kangaroo Care on Body Temperature Stability of Low Body Weight : Literature Review - Ruminem, Ruminem; Adawiyah, Jamiatul; Widiastuti, Ida Ayu Kade Sri; Sari, Rita Puspa; Ramadhani, Siti (Fakultas Kedokteran, 2022)
Background : Low Birth Weight Babies (LBW) are babies born with birth weight <2500 grams regardless of gestational age. One of the complications of LBW is the instability of body temperature, so to maintain its stability the kangaroo method of care is used. The purpose of this study is u ntuk identify and analyze articles related to the kangaroo method of treatment influences the stability of the baby's body temperature LBW. Methods of study : This study is a literature review premises using the 3 articles that are tailored to the inclusion criteria and were analyzed methods critical appraisal . Research Results : Based on the results of the research, the three articles showed that the characteristics of the majority of respondents were female, aged 3-28 days and the majority weighed 1500-2000 grams. There is a difference in body temperature of LBW babies before and after Kangaroo Method Treatment and there is an effect of Kangaroo Method Care on the stability of the body temperature of LBW babies. Conclusion : There is differences in body temperature of LBW before and after being given kangaroo method treatment and there is an effect of kangaroo method care on body temperature of LBW babies..